2000
DOI: 10.1056/nejm200011303432203
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fecal Occult-Blood Screening on the Incidence of Colorectal Cancer

Abstract: The use of either annual or biennial fecal occult-blood testing significantly reduces the incidence of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
637
2
44

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,249 publications
(698 citation statements)
references
References 30 publications
15
637
2
44
Order By: Relevance
“…In the United States, practice of colorectal cancer screening is excellent, achieving 90-95% of health care providers recommending screening (Task Force 2002). Our study results showed that CRC screening is underutilized as more than half of the study subjects were not practicing CRC screening in spite of the documented survival benefit from CRC screening (Klabunde 2003, Mandel 2000and Hardcastle 1996. This can be attributed to lack of information and knowledge among the doctors about the recommended screening guidelines and poor awareness about the timing of initiation of screening and its benefits.…”
Section: Discussionmentioning
confidence: 81%
“…In the United States, practice of colorectal cancer screening is excellent, achieving 90-95% of health care providers recommending screening (Task Force 2002). Our study results showed that CRC screening is underutilized as more than half of the study subjects were not practicing CRC screening in spite of the documented survival benefit from CRC screening (Klabunde 2003, Mandel 2000and Hardcastle 1996. This can be attributed to lack of information and knowledge among the doctors about the recommended screening guidelines and poor awareness about the timing of initiation of screening and its benefits.…”
Section: Discussionmentioning
confidence: 81%
“…3 A and B, showing incidence by birth cohort in various age groups, also exhibit shifting peaks near calendar year 1985. The increase in incidence by calendar year may be related to improved screening for colon cancer, whereas the drop after 1985 could be due to the gradual wearing off of the resulting ''harvesting'' effect (31).…”
Section: Resultsmentioning
confidence: 99%
“…Presymptomatic detection of localized cancer will result in a reduction in morbidity and/or mortality [6,7,8]. If screening detects preinvasive lesions, namely dysplasia, it will reduce cancer incidence [9]. …”
Section: Justification Of New Test Developmentmentioning
confidence: 99%